Genetic Variability Studies in Field Pea (Pisum sativum L.) for Yield and Associated Characters Evaluated at Asasa South-East Highlands of Ethiopia - Abo, Temesgen; Mohamed, Wassu (International Journal of Bio-resource and Stress Management, 2025)
The current study was conducted during June to October, 2019 cropping season at Asasa, Ethiopia to evaluate forty-nine field pea genotypes were evaluated in simple lattice design to assess genetic variability for morpho-agronomic traits. The analysis of variance showed significant differences among genotypes for most of the traits. The genotypes variations for grain yield in the range between 383.0 to 5605 kg ha-1. A total of 10 genotypes had higher grain yield than high yielding check variety, Burkitu (4521 kg ha-1) of which EH 010011-3, EH 08003-2 and EH 08016-2 had 24, 14.80 and 14.11% yield advantages, respectively, over higher yielding check variety. The mean performance of genotype EH010011-3 was highest at Asasa with mean grain yield 5605 kg ha-1. The genotypic coefficient of variation ranged from 1.0% for days to maturity to 20.01% for grain yield, whereas the phenotypic coefficient of variation ranged from 1.37% for days to maturity to 27.41% for grain yield ha-1. The estimated broad sense heritability ranged from 51.21% for thousand seed weight to 53.93% for days to maturity. Genetic advance as percent of mean ranged from 1.52% for days to maturity to 33.88% for grain yield. The study showed the existence of reasonable genetic variability among the field pea genotypes that could be exploited in breeding programs.